PENDIDIKAN DALAM URUSAN RUMAH TANGGA (SEBUAH ANALISIS HADIS RASUL) - Purwidianto Purwidianto (Universitas Muhammadiyah Prof Dr Hamka, 2016)
The coming of the Prophet Muhammad is a mercy for all mankind (rahmatan lil alamin). Anything that is taught by the Prophet in the Hadith is the embodiment of that mission. so that if the teachings of Islam that comes from the prophet violate that principle should be straightened. One is seated husband and wife as an object as a subject in the relationship in the household, including the sexual relations between husband and wife. The situation is sometimes ignore the principle mu'asyarah bil ma'ruf, even the actors sometimes feel right because he felt what he did was based on religious texts. This study seeks mendudukan hadith related sexual relations between husband and wife on the correct understanding that does not undermine one of the two. so that the traditions related to the prohibition of solicitation husband wife refuses sexual relations do not become a tool of legitimacy for the husband to act arbitrarily against his wife because sexual relations between husband and wife is not just a matter of mere biological, but also psychological.